Gallium Methylene. Issue 24 (9th May 2019) - Bonath, Martin; Maichle‐Mössmer, Cäcilia; Sirsch, Peter; Anwander, Reiner
Abstract: Despite the eminent importance of metal alkylidene species for organic synthesis and industrial catalytic processes, molecular homoleptic metal methylene compounds [M(CH2 ) n ] as the simplest representatives, have remained elusive. Reports on this topic date back to 1955 when polymeric [Li2 (CH2 )] n and [Mg(CH2 )] n were accessed by pyrolysis of methyllithium and dimethylmagnesium, respectively. However, the insoluble salt‐like composition of these compounds has impeded their application as valuable reagents. We report that rare‐earth metallocene methyl complexes [(C5 Me5 )2 Ln{(μ‐Me)2 GaMe2 }] (Ln=Lu, Y) trigger the formation of homoleptic gallium methylene [Ga8 (μ‐CH2 )12 ] from trimethylgallium [GaMe3 ] (Me=methyl) via a cascade C−H bond activation involving the dodecametallic clusters [(C5 Me5 )6 Ln3 (μ3 ‐CH2 )6 Ga9 (μ‐CH2 )9 ] as crucial intermediates. Such gallium methylene compounds feature a reversible [Ga8 (μ‐CH2 )12 ]/[Ga6 (μ‐CH2 )9 ] oligomer switch in donor solvents and act as Schrock‐type methylene‐transfer reagents. Abstract : Rare‐earth‐metal methyl moieties react with trimethylgallium via a cascade of C−H bond activation steps. The resulting product is the first molecular homoleptic metal methylene complex. It engages in a reversible [Ga8 (μ‐CH2 )12 ]/[Ga6 (μ‐CH2 )9 ] oligomer switch.